Integrated pest management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A group of Dutch NGOs working on rural development and environmental protection is currently assessing the demand for an information and documentation service on integrated pest management in the tropics. People interested in such a service, those...